Devaluation expectations for the IR#/DM in the EMS: some empirical estimates and their relation to fundamentals - O'Donnell, Mary (Economic & Social Studies, 1995)
This paper presents results for devaluation expectations for the IR#/DM for the period of EMS membership. The methodology employed produces estimates of expected rates of devaluation by adjusting the interest rate differential by the expected rate of depreciation within the band. These estimates are then related to economic fundamentals. Expected rates of devaluation are found to be positively correlated with the IR#/Stg exchange rate and marginally related to unemployment, the level of reserves and the balance of payments surplus.
Keywords: European Monetary System; Devaluation; Irish punt; Deutschmark